ASPECTS IN ANTERIOR OPEN BITE CORRECTION IN A GROUP OF ORTHODONTIC PATIENTS - Daniela Anistoroaei; Loredana Golovcencu; Georgeta Zegan; Alina Claudia Sodor Botezatu; Eduard Radu Cernei; Alexandra Stan; Cătălina Iulia Săveanu (Romanian Journal of Oral Rehabilitation, 2023)
Aim of the study. The aim of the study was to analyse the type and the effectiveness of orthodontic treatment for anterior open bite (AOB). Material and methods. A study group of 52 patients with anterior open bite (AOB) were analysed according to age, gender, type of dentition and Angle classes of malocclusion. The type of anterior open bite, the type and treatment stages were analysed the, through descriptive statistics. Results. The anterior open bite was recorded in: 59.6% girls and (40.4%), boys, in 46,2% patients with mixed dentition and in 53.8% patients with permanent dentition and in 9.6% patients with Angle class I malocclusion, 34.6% with Angle class II malocclusion, 55.8 % patients with Angle class III malocclusion. AOB was functional in 38.5% patients and skeletal in 61.6% patients. A multitude of appliances have been used for the treatment of AOB in one (48.1%), two stages (46.2%) or combined with orthognathic surgery (5.8%). Statistically significantly correlation was found between AOB and age (p= 0.002), type of dentition (mixed or permanent) (p = 0.000). Also, statistically significant correlations were obtained between type of treatment and type of dentition (p = 0.000) and with treatment stages and Angle classes of malocclusion (p = 0.000). Conclusion. The treatment of AOB requires the selection of the most appropriate treatment method in accordance with the severity of the malocclusion, the age of the patient.